Clinical clearance of complex basal cell carcinoma in patients receiving sonidegib: A case series. Issue 2 (6th December 2021) - Leow, Liang Joo; Teh, Natalie
Abstract: Basal cell carcinoma (BCC) is the most common cancer worldwide. While most BCC cases respond to surgical management, complex BCC often presents treatment challenges for patients unsuitable for, or refractory to, surgery and radiotherapy—limiting treatment options. Hedgehog pathway inhibitors (HHI) have emerged as an important treatment option for patients with complex BCC—providing a durable treatment modality and improved clinical outcomes. We present a case series of 10 patients with complex BCC treated with sonidegib, an oral HHI, at a dose of 200 mg once daily for a mean duration of 6 months and a mean follow‐up of 7 months. Of these patients, sonidegib monotherapy was curative in eight cases. Of the remaining two patients, treatment with sonidegib arrested tumor progression and decreased tumor size to a point where surgical removal was straightforward. The positive treatment response we observed supports use of sonidegib as an effective treatment option for patients with complex BCC.